Cultural Beliefs of Turkish Women for Breast Cancer and Screening - Tosun, Hale; Andsoy, Işıl Işık; GÜL, ASİYE (SAGE Publications Inc., 2021)
Introduction: Breast cancer is an important health problem and early diagnosis is important in its treatment. Women's approach and cultural beliefs are effective in ensuring early diagnosis. This study examined psychometric properties of the Ferrans Cultural Beliefs Scale and assessed cultural beliefs on breast cancer and screening programs among Turkish women. Method: The study was performed in a descriptive and cross-sectional design with 420 women using the Ferrans Cultural Beliefs Scale that is considered reliable and valid in Turkey. Results: The mean total score of the Ferrans Cultural Beliefs Scale was 3.24 +/- 3.16. The highest "yes" responses were for the statement "If breast cancer is treated correctly, it can be cured" (n = 387, 92.1%). Discussion: This study, which is the first in Turkey, highlights the importance of measuring the effects of Turkish healthy women's cultural beliefs in breast cancer and screening for early diagnosis. Determining women's cultural beliefs will make known the attitudes and behaviors toward breast cancer, so that the nurse will provide sensitive and effective nursing care, develop nursing knowledge, and integrate this knowledge with clinical practice.
Keywords: Breast Cancer; Cultural Beliefs; Turkish Women; Validity; Reliability